If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6 = -48 Reorder the terms: -6 + 3x = -48 Solving -6 + 3x = -48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 3x = -48 + 6 Combine like terms: -6 + 6 = 0 0 + 3x = -48 + 6 3x = -48 + 6 Combine like terms: -48 + 6 = -42 3x = -42 Divide each side by '3'. x = -14 Simplifying x = -14
| 3z=2.8+0.5 | | 210.00x+0.25=380.00 | | a/3.5-4.8=6.8 | | 45=12y-3y | | 3x-9=-2x-1 | | 2b^2-10b-12= | | Y=15-2/3x | | 18+n=40 | | 14(10x+9)=-19(x-4) | | 7x-70=5x+10 | | 5s+8=-10+7s-2 | | -8x+5=-155 | | Artan(0.44469726).180= | | -4u+2(u-5)=-28 | | x/2-2=11 | | 12(-12x+6)=25(x-2) | | 9/10x=9/11 | | -6+3y=-3+6y | | 20(6x+7)=-5(x-5) | | 9b+8=-8-7b | | -6x+5=3+5x | | 9(3x-23)=1(x+5) | | -4-4c=6-2c | | 4x^3-12x^2-4X=0 | | 5e^2x-1-3=12 | | 8q-5=9q | | 1.9=9.1-0.9x | | -3(2b-5)=2b | | 19(3x-6)=25(x+2) | | -9h=-10h+10 | | 4r^2-16r-128= | | 125=8-3x |